ANALYZING THE INFLUENCE OF ATTITUDE TOWARDS SPONSOR AND SPONSORSHIP AWARENESS TO PURCHASE INTENTION IN MANADO (CASE STUDY: MOTOGP) - Rondonuwu, Christin (Sam Ratulangi University, 2015)
ABSTRACT The use of Sponsorship has increased in recent years, especially in Sports Sponsorship. Several teams participating in MotoGP were sponsored by local Indonesian companies as majority of the audience were from Indonesian. In order to determine how consumer’s attitude towards sponsor and sponsorship awareness would affect consumer’s purchase intention, MotoGP was used as a case study. A survey research was conducted in Manado, with sample size of 70 respondents that consist of 51 male respondents and 19 female respondents. Research data was quantitative analyzed and presented. The result of this research shows that there is partial and simultaneous influence from consumer’s attitude towards sponsor and sponsorship awareness on consumer’s purchase intention in Manado. Keywords: Purchase Intention, Attitude towards Sponsor, Sponsorship Awareness, MotoGP.